Kerja Sama Antar Umat Beragama: Pilihan Masyarakat Majemuk - Machasin, - (Unisia, 2016)
Religion is a way of life by which God give to the mankind in order to make them aware their humanity and their duty to worship God. But we are facing the condition in which in the name of God and religion, people kill each other due to their pity and narrow mind in understanding their religion. Religion decreasing in its meaning to merely a tradition of the religion and few religious leaders take benefit from this situation to maintain his domination in society. Religious followers shouldn’t have perception that people from different religions are their enemy as long as they do not make any hurts towards their belief and activities, and again, people should not force their belief to people of different religions. Interfaith relation should be based on the duty that people must respect each other and working together in the field of human relation very homogen society without loosing their belief, as the meaning of religion is to bring people to humanity and peace.